Eclat - Boulez, Pierre 1925-2016 (Juxtapositions, 2006)
Eclat is a real study of resonance written for fifteen instruments Pierre Boulez created in 1965, a glittering jewel of tightness and rationality, a riotously colorful mixture of open-form freedom and serialist order. Eclat (meaning to "burst out") is a kind of "concerto for conductor", where the musicians in the ensemble play semi-improvisational material prescribed within boxes in Boulez's score. Given this material, the conductor "composes" and controls the work via an elaborate and complex series of cues, directing the content of the music and deciding which musicians play when, as well as what they play. In this film by Frank Scheffer, Eclat is performed by the Netherland's Nieuw Ensemble conducted by Ed Spanjaard , coached by Boulez himself. (Covertext)